Narcotics Anonymous: Anonymity, Admiration, and Prestige in an Egalitarian Community. (December 2014) - Snyder, Jeffrey K.; Fessler, Daniel M. T.
Abstract Narcotics Anonymous (NA) supports long‐term recovery for those addicted to drugs. Paralleling social dynamics in many small‐scale societies, NA exhibits tension between egalitarianism and prestige‐based hierarchy, a problem exacerbated by the addict's personality as characterized by NA's ethnopsychology. We explore how NA's central principle of anonymity normatively translates into egalitarianism among group members. Turning to the lived reality of membership, building on Carr's (2011) concept of script flipping, we identify script embellishment as speech acts that ostensibly conform to normative therapeutic discourse while covertly serving political ends. We argue that, in spite of the overtly egalitarian context, NA members differ dramatically in prestige, with more experienced members being admired and emulated. Critically, prestige acquisition occurs via structural functions that are central to the maintenance of the institution, as experienced members serve a central role in the transmission and enforcement of cultural norms, paradoxically including norms of egalitarianism.